Gender difference in nutrition and health in agricultural households in Nigeria: The role of corporate social responsibility in oil producing communities - Joseph I. Uduji; Elda N. Okolo-Obasi (African Governance and Development Institute (AGDI), 2022)
The purpose of this paper is to critically examine the multinational oil companies' (MOCs) corporate social responsibility (CSR) initiatives in Nigeria. Its special focus is to investigate the impact of the global memorandum of understanding (GMoU) on gender difference in nutrition and health in the Niger Delta region of Nigeria. This paper adopts a survey research technique, aimed at gathering information from a representative sample of the population, as it is essentially cross-sectional, describing and interpreting the current situation. A total of 800 women respondents were sampled across the rural areas of the Niger Delta region. The results from the use of a combined propensity score matching and logit model indicate that CSR of the MOCs using GMoU model has made significant success in closing the gender difference in nutrition and health in agricultural household in the Niger Delta region. The findings also show that mainstreaming gender in nutrition within the field of agriculture is a critical aspect of strengthening gender and nutrition/health linkages, in recognition of women substantial contribution to agriculture production and their central role in household food collection, preservation/processing and preparation. This suggest that mainstreaming gender in nutrition offers opportunities to integrate agriculture and health approaches in GMoU projects, which will require increased collaboration and coordination between the MOCs' and CBD clusters in the field of gender and nutrition to exploit existing complementary and comparative advantages, and to apply a holistic approach in host communities. This implies that gender and nutrition/health have multiple dimensions and are highly context-specific; and the pathway towards improved food and nutrition security for all should be a gender-equitable process incorporated in CSR programmes and projects in sub-Saharan Africa. This research contributes to the gender debate in agriculture from a CSR perspective in developing countries and rationale for demands for social project by host communities. It concludes that business has an obligation to help in solving problems of public concern.
Keywords: 330; Gender; nutrition and health; agricultural households; corporate social responsibility; multinational oil companies; sub-Saharan Africa